(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In modern conditions of modernization, in particular, the modernization of Kazakhstan’s The status of religion is determined by the processes secularization, desecularization, de- and resacra- lization and religious deconstruction, dualization of religion. The above processes are indicators of the degree of religiosity, first of all, society.